Background and Major Choice in Tertiary Education: Evidence from Ireland - Crotty, Dáire (The Economic and Social Review, 2025)
While prior research has established a strong link between background and academic success, the impact of background on specific academic decisions, particularly college major choices, remains less explored. With the use of the Growing Up in Ireland dataset, I investigate whether children from different backgrounds make systematically different college choices from each other. Applying a multinomial logistic regression, I find that background measures such as parental education and income impact choices in several college majors. Maternal education is significantly associated with choosing Education and Arts and Humanities, while household income significantly influences choices in Social Sciences. Robustness checks indicate that these relationships differ by gender and type of tertiary institute, with the definition of background considerably impacting the shape and significance of estimates. Overall, the findings from this paper highlight the need for targeted policies to support students from disadvantaged and less educated backgrounds. Such policies may need to be major-specific to ensure equal opportunities for all students.